Culturally responsive L2 education : an awareness-raising proposal - Porto, Melina (2010)
The increasing prevalence of multilingual, multiethnic, and multicultural classrooms in varied educational contexts worldwide points to the importance of cultural factors in language education and education in general. In the EFL/ESL classroom of this century, ELT is seen as including much more than purely linguistic aspects as it focuses also on broad literacy issues which acknowledge the importance of global economic, social, historical, and cultural factors in language learning and teaching. In other words, ELT in the twenty-first century means culturally responsive literacy education. It is argued here that foreign/second language education viewed in these terms requires cultural responsiveness in educators. This paper will offer a concrete proposal aimed at raising foreign language educators' awareness of this topic.
Keywords: Culture; ELT; Teacher education; Awareness-raising proposal